Tradisi Pembacaan Surah Waqi’ah Studi Living Qur’an di Pondok Pesantren An-Nur 2 Al Murtadlo: Perspektif Living Qur’an Teori Fenomenologi Alfred Schutz - Hamada Syahrul Hufron; Basri; Muhammad (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research study discusses the study of living Qur'an in the tradition of reading, Surah Al-waqi'ah at the An-nur 2 Al Murtadlo Islamic Boarding School, reading Surah Al-waqi'ah is a mandatory activity every day before performing the Ashar prayer, especially for male students. This study aims to reveal the Tradition of Reading Surah Al-waqi'ah at the An-nur 2 Al Murtadlo Islamic Boarding School with the formulation of the problem: (1) How is the Implementation of the Al-waqi'ah Reading tradition (2) How is the realization of the impact of reading Surah Al-waqi'ah on students. This study, qualitative descriptive research with the Alfred Schutz Phenomenology approach as a different analysis knife. data collection techniques with observation, interview and documentation techniques. The research informants were students of An-nur 2 Al Murtadlo, the data processing used qualitative descriptive techniques. The results of this study: 1) Implementation of the tradition of reciting Surah Al-Waqi'ah as a daily practice before the Asr prayer, because the Asr time is believed to be a time of efficacy, based on the interpretation of the Qur'an Surah Al-'Ashr, the implementation of reciting Surah Al-Waqi'ah begins with reciting tawassul, Al-Waqi'ah, وصبّ عليّ الرّزق, أَوْ كَالَّذِي مَرَّ عَلَىٰ قَرْيَةٍ, and is closed with the Al-Waqi'ah prayer. 2) The reading of Surah Al-waqi'ah at the An-nur 2 Al Murtadlo Islamic Boarding School is a mandatory activity there, the motives for the purpose of reading Surah Al Al-waqi'ah are to get closer to Allah, hope for blessings, discipline time and preserve the Qur'an. The impacts felt by the students, teachers and administrators of this tradition are that their livelihood becomes smooth, they feel peace of mind, and their wishes are made easier.